Relaxation & breathing for meditation [videorecording (DVD)] : with Rodney Yee - Yee, Rodney; Landon, Ted; Cogozzo, Linda; Davidson, Peter; McEachen, Jim; Webber, Charlie (Gaiam, 2003)
This program teaches "conscious relaxation" and "conscious breathing" to improve sleep and create an overall sense of well-being.